Educational Games in Arabic Language Learning: A Meta-Analysis of Outcomes and Moderating Factors - Muhammad Yahya Abdullah; Amanda Putri; Syauqi Miftahul Karim; Habib Luthfi; Mahfudhotul Firdaus; Nabil Gustian (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This study examined the effectiveness of educational games in Arabic language learning through a meta-analysis of 38 independent effect sizes from empirical studies conducted in various educational contexts. A random-effects model was used to estimate the overall effect and analyze moderator variables, including school level, country, language skill, game type, and sample size. The results showed a statistically significant and large overall effect of educational games on Arabic language learning outcomes (SMD = 1.649, 95% CI = 1.303–1.996, p < .001). However, substantial heterogeneity was found among the studies (I² = 93.02%), indicating variation across educational contexts. Subgroup analyses revealed positive effects across all moderator categories. The largest effects were identified among primary school students, studies conducted in Saudi Arabia, and interventions targeting speaking, listening, and writing skills. Traditional educational games produced slightly larger effects than digital games. Sensitivity analysis confirmed the robustness of the findings, although PET-PEESE analysis indicated the presence of publication bias and small-study effects. Overall, the findings suggest that educational games are a promising instructional approach for improving Arabic language learning outcomes across different educational settings. This study also contributes to Arabic language education research by identifying contextual factors associated with variations in learning outcomes.